Monostotic fibrous dysplasia of the orbit: an unusual lacrimal fossa mass. - McCluskey, P (1993)
A case of monostotic fibrous dysplasia involving the orbit, presenting with a short history of painful, progressive proptosis and a lacrimal fossa mass is reported. There were no clinical or radiological clues to the diagnosis which was made on frozen section at the time of open surgical biopsy. The features of orbital fibrous dysplasia are reviewed and a possible mechanism for this rare clinical presentation of fibrous dysplasia is discussed.